The human rights dictatorship : socialism, global solidarity and revolution in East Germany - Richardson-Little, Ned 1983- (Human rights in history, 2020)
Klappentext: "Richardson-Little exposes the forgotten history of human rights in the German Democratic Republic, placing the history of the Cold War, Eastern European dissidents and the revolutions of 1989 in a new light. By demonstrating how even a communist dictatorship could imagine itself to be a champion of human rights, this book challenges popular narratives on the fall of the Berlin Wall and illustrates how notions of human rights evolved in the Cold War as they were re-imagined in East Germany by both dissidents and state officials. Ultimately, the fight for human rights in East Germany was part of a global battle in the post-war era over competing conceptions of what human rights meant. Nonetheless, the collapse of dictatorship in East Germany did not end this conflict, as citizens had to choose for themselves what kind of human rights would follow in its wake"--